EVALUATION OF THE IMPLEMENTATION OF THE ISLAMIC RELIGIOUS EDUCATION CURRICULUM AT STATE ELEMENTARY SCHOOL 32 TALANG UBI, PALI - Siska Septia Ulfa; Yulia Tri Samiha; Afriantoni Afriantoni; Yuniar Yuniar (Jurnal Konseling Pendidikan Islam, 2026)
This research evaluates the Islamic Education (PAI) curriculum management at SDN 32 Talang Ubi PALI using the CIPP model. A mixed-method approach was employed, combining qualitative and quantitative descriptive data from 175 respondents. Context evaluation (criteria: background, problems, opportunities) scored 16.14%, revealing a vision-practice gap despite management's openness to integrating Islamic values into Kurikulum Merdeka. Input (criteria: teacher competence/readiness) scored 20.21%, revealing digital proficiency but hindered by non-integrated modules, the lack of child protection SOPs, and the absence of a prayer room (mushola). Process (criteria: procedures, methods, supervision) scored 23.99%, indicating inclusive activities though still lecture-dominant, with weak physical documentation and low parental synergy (9.15%). Product (criteria: cognitive, affective, psychomotor) scored 19.99%, noting good learning outcomes, yet character habituation remains inconsistent and lacks independent worship monitoring tools. Overall, curriculum management is categorized as Good (80.33%). Recommendations include building a prayer room, formalizing child protection policies, optimizing gamification, and developing a worship monitoring app to maintain character continuity between school and home.